Opinions of Social Workers in Turkey About the Principles on Die with Dignity - Duyan, Veli (Journal of religion and health, 2016)
The conditions how people will spend their very last moments are an increasingly debated topic in Turkey. This study is planned to learn the opinions of Social Workers in Turkey on “Principles of a good death.” The results of this study reveal that social workers in Turkey agree with principles of a good death in general. The degree of support for some specific principles changes by the sex and age of the participants. Despite the significant support given to principles by social workers, majority of them do not think that these principles are currently followed in medical and care institutions in Turkey.